Jurnal PKM : Pelatihan Wirausaha Menggunakan Tokopedia Bagi Ibu-Ibu Rumah Tangga Bekerjasama Dengan Rumah Keluarga Indonesia Kecamatan Karang Tengah - Kota Tangerang: Entrepreneurship Training Using Tokopedia for Housewives in Cooperation with Rumah Keluarga Indonesia Karang Tengah District - Tangerang City - Noni Juliasari; Sri Mulyati; Safrina Amini (DRPM Universitas Budi Luhur, 2021)
Today's household needs demand adequate economic sufficiency. Indeed, even though she is a housewife, she can still work and also earn income other than gifts from her husband so that she can still work from home. Various kinds of business models today can be managed from home while still taking care of the household. Especially with the penetration of information and communication technology in even the smallest aspects of life, it has become possible. So that many housewives continue to work and have an income, one of which is through an online business. Through this training, we want to make housewives who want to increase their income for their household income through online entrepreneurship, one of which is by utilizing the features available on tokopedia.com. It is hoped that the training will be able to provide additional skills for housewives, and especially the benefits can be felt to improve their economy.